Study of the interaction between cement phases and polycarboxylate superplasticizers possessing silyl functionalities - Plank, Johann; Yang, Fan; Storcheva, Oksana (Journal of sustainable cement based materials, 2014)
In 1981, polycarboxylate comb polymers were introduced as a new class of superplasticizers. Their structural characteristic is an anionic polymer backbone, which holds lateral graft chains. These side chains instigate a steric hindrance effect between the cement particles suspended in water. In spite of the great arsenal of currently available PCE products, the industry tries to further improve this technology. The main goal is to present novel PCE structures which are more robust with diverse cement compositions, which are not subject to desorption by free dissolved sulfate and which can tolerate contaminants such as clay minerals. In this study, PCEs possessing silyl functionalities were synthesized and their dispersion effectiveness, working mechanism, and interaction with cement surface were investigated. For this purpose, MPEG-type PCEs containing silyl functionalities were prepared by free radical copolymerization from methacrylic acid, MPEG methacrylate ester, and N-maleic acid-γ-aminopropyl triethoxy silane at different molar ratios. The polymers were characterized with respect to their elemental composition, molar masses (M w , M n ), polydispersity index, and anionic charge amount. Dispersion effectiveness of the silylated PCEs was probed via 'mini slump' test on cement pastes. Adsorption of these polymers on cement and pure C 3 S clinker phase was quantified to identify the working mechanism. The silylated PCEs were found to exhibit superior dispersing performance, which is explained by their increased adsorption. Owed to this higher initial adsorption, slump retention decreased compared to a similar, non-silylated PCE polymer. Robustness of these PCEs against sulfate was investigated by a desorption experiment using K 2 SO 4 . It confirmed that silylated PCEs possess higher sulfate tolerance than conventional PCEs. Furthermore, 29 Si CP MAS NMR spectroscopy provided evidence for a chemical bond between the polymer and the surface of C-S-H phases. The study demonstrates that silyl-modified PCE superplasticizers present highly effective cement dispersants, which work at low dosages. Their superior performance can be explained by the formation of chemical bonds between the silyl functionalities of the PCEs and hydrated silicate phases of cement. Originality The purpose of synthesizing PCEs with silyl functionalities was to clarify whether such PCEs can interact with the surfaces of the silicates present in cement. Common anionic superplasticizers adsorb almost exclusively on aluminate hydrates such as ettringite or monosulfo aluminate. The silanol groups formed after alkaline hydrolysis of the siloxane functionality contained in those PCEs can undergo a condensation reaction with ≡Si-OH groups present on the surfaces of hydrated C 3 S and C 2 S. The aim was to obtain a PCE which is not only physically sorbed, but chemically bound to cement through a covalent bond. This way silyl-grafted PCEs would be robust against desorption from sulfate and thus can exhibit a more stable performance.